Spotlight - Report On An International Conference: Mineral Processing - Recent Advances And Future Trends - M. H. Moys (The Southern African Institute of Mining and Metallurgy, 1996)
I had the good fortune to attend the above Conference which was held in Kanpur, India, on 11-15 December, 1995. The Conference was held in honour of Professor P.C. Kapur of the Indian Institute of Technology in Kanpur. Professor Kapur was one of the early students of legendary teacher and researcher of mineral beneficiation, Professor Doug Fuerstenau of the Department of Materials Science and Engineering at the University of California at Berkeley. I have attended my fair share of international conferences and this one certainly rated at the top of the list on several counts. With an open-hearted hospitality which one might almost take for granted once you have spent some time in India, the organizers of the Conference looked after every need of their guests, including breakfast and transport to and from the conference centre, wonderful traditional lunches and dinners and outstanding entertainment in the evenings. The papers were generally of a high standard, and debate flowed enthusiastically and freely. Several international guests delivered seminal papers in their fields as discussed below.